Facial neuritis in coronavirus disease 2019 associated mucormycosis: study on clinico-radiological correlates. Issue 4 (31st January 2022) - Jaiswal, A S; Sikka, K; Bhalla, A S; Manchanda, S; Goel, G; Verma, H; Thakar, A
Abstract: Objective: To elucidate the aetiopathogenesis of facial neuritis in coronavirus disease 2019 associated mucormycosis. Methods: A retrospective review was conducted of coronavirus disease 2019 associated mucormycosis patients who presented with peripheral facial nerve palsy from January 2021 to July 2021. The clinico-radiological details of four patients were assessed to examine the potential mechanism of facial nerve involvement. Results: Serial radiological evaluation with contrast-enhanced computed tomography and contrast-enhanced magnetic resonance imaging revealed infratemporal fossa involvement in all cases, with the inflammation extending along fascial planes to reach the stylomastoid foramen. Ascending neuritis with an enhancement of the facial nerve was demonstrated in all cases. Conclusion: The likely explanation for facial palsy in patients with coronavirus disease 2019 associated mucormycosis, backed by radiology, is the disease abutting the facial nerve at the stylomastoid foramen and causing ascending neuritis of the facial nerve.